AT THE CROSSROADS OF THE REAL AND THE FANTASTIC: A COMPARATIVE STUDY OF IDENTITY, HISTORY, AND DESTINY IN SALMAN RUSHDIE'S MIDNIGHT'S CHILDREN AND ANGELA CARTER'S WISE CHILDREN - Petru Ștefan IONESCU (Incursiuni în imaginar)
This research paper provides an exploration of the complex and reciprocal relation between identity, history, and destiny in Salman Rushdie's Midnight's Children and Angela Carter's Wise Children. We regard these two works as exemplary in their use of magical realism, not merely as a stylistic device, but also as a powerful narrative tool that helps define the complexities of human existence. Through a comparative analysis, this paper examines how Rushdie and Carter blend the real with the fantastical to challenge conventional narratives, exploring the intricate nature of identity and the dynamic reciprocity between personal and collective histories. In Midnight's Children, Rushdie blends the life of his protagonist, Saleem Sinai, with the historical reality of postcolonial India, using magical realism to blur the boundaries between the personal and the national, the real and the imagined. The novel’s non-linear structure and fragmented narration reflect the tumultuous and often contradictory nature of postcolonial identity, illustrating how personal and national histories are intertwined and constantly evolving. The midnight's children, born at the exact moment of India’s independence, symbolize the nation’s future potential but also its inherent complexities, their supernatural abilities serving as metaphors for the highly diverse and complex nature of Indian identity. On the other hand, Angela Carter’s Wise Children explores identity using performance and theatricality, focusing on the lives of Dora and Nora Chance, the illegitimate daughters of a famous Shakespearean actor. Carter’s narrative style, characterized by its playfulness and subversive humor, uses magical realism to blur the lines between reality and performance, suggesting that identity is as much a construction and performance as any role played on stage. The Chance sisters’ improbable survival and their lives filled with theatrical performances and fantastical elements highlight the fluidity of identity and the artificiality of social constructs such as legitimacy and lineage. Children play an extremely important role in both novels, their symbolism lying at the core of both narratives. Opposing the reality of the adult world to the fantastic freedom of childhood, with its lack of imaginative boundaries, the novels question the nature of reality and our accepted worldview. This study draws on the primary literature, analyzing the two mentioned works, but also on a wide range of secondary literature, including postcolonial theory, feminist criticism, and narrative theory, to situate the analysis within broader cultural and literary contexts. Homi K. Bhabha's concept of hybridity is particularly relevant in understanding the fragmented identities in Midnight's Children, while Judith Butler's theory of performativity offers insights into the fluid identities portrayed in Wise Children. By examining the symbolic roles of children in both novels, the research highlights how Rushdie and Carter use magical realism to explore and critique the constructed nature of identity, history, and destiny. Ultimately, this study argues that magical realism in these novels is not simply a narrative style but a powerful tool for exploring the complexities of identity and history in postcolonial and feminist contexts. Midnight's Children and Wise Children both challenge the linear, teleological narratives of history and identity, offering instead a vision of reality that is many-sided, fluid, and constantly being rewritten. Through their use of magical realism, Rushdie and Carter create narratives that invite readers to question conventional understandings of the self, society, the present and the past, offering new possibilities for the ways in which we understand identity, history, and destiny.